POTENSI DAN KEKAYAAN Ficus spp. PADA ZONA REHABILITASI BLOK PASIRBATANG DI TAMAN NASIONAL GUNUNG CIREMAI KABUPATEN KUNINGAN - Yayan Hendrayana (Scripta Biologica, 2022)
The Pasirbatang rehabilitation zone is part of the Ciremai Mountain National Park (TNGC) which is on the south side has experienced degradation. Therefore, planting was carried out in this zone with local species in 2014. The purpose of this study was to determine the vegetation structure and richness of the Ficus clan in the rehabilitation zone. This research was conducted in July-September 2018 with the method of placing the sampling plot on the specified path. A total of 31 species were found at various levels of growth with the Important Value Index (IVI) at the tree level (192.12%) in the form of Pinus merkusii, pole level (66.38%) in the form of Nauclea lanceolata, sapling level (141.72%) and seedlings (148.69%) in the form of Caliandra callothyrsus. Potential of Ficus spp is spread in various growth rates, namely species of F. septica, F. ampelas, F. variegata and F. fistulosa with the highest density at seedling level (166 ind / ha), and followed by sapling levels (64 ind / ha), poles (16 ind / ha) and trees (0.67 ind / ha). This Ficus wealth is considered important for the zone rehabilitation program in the Mount Ciremai National Park